Perancangan dan Pengembangan Produk Daun Pintu Ukiran yang Berorientasi pada Preferensi Konsumen dengan Konsep Rekayasa Nilai - Titik Noorida, Soffa (Jurnal Teknik Industri, 2000)
The grouith of Jepara traditional architecture that begins too advanced now days had caused appearing ideas for the writer to creat design creation from Jepara architecture building component that is modern traditional. Desaigning and developing Jepara architecture component production is especiallied on a door carving only. The creation that will be developed is the improvement of combination of the material usage that becomes the basic material.